2011
DOI: 10.1071/aj10013
|View full text |Cite
|
Sign up to set email alerts
|

A new, field-proven, cost-effective solution for MEG regeneration unit issues in offshore Australia gas production

Abstract: Several gas fields are being developed off the coast of Western Australia. The risk for hydrate blockages in these fields is high and presents several challenges for hydrate inhibition, including high subcoolings, low water salinities, and high system temperatures. The current strategy is to use mono-ethylene glycol (MEG) for hydrate inhibition, which includes MEG regeneration units (MRUs) in the design of the facilities. The installation and maintenance of MRUs capable of handling the large required volumes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Challenges encountered in deep-water fields include colder water, longer subsea tiebacks, higher water cuts, and higher hydrostatic pressure, thereby increasing risks of plugging pipelines because of hydrate formation, wax/asphaltene precipitation, or scaling. , Hydrate flow assurance is a major technical concern by the flow assurance engineers in deep-water fields. Thermodynamic hydrate inhibitors (THIs) injecting or heating have been widely applied in flowlines to shift the operation condition outside of the hydrate formation boundary, making it thermodynamically unfavorable for hydrate formation. These methods are effective, but a large amount of additives is required to be injected and huge energy is needed for heating, which make them financially unattractive . Alternatively, a risk management method is presented to control hydrate blockage issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Challenges encountered in deep-water fields include colder water, longer subsea tiebacks, higher water cuts, and higher hydrostatic pressure, thereby increasing risks of plugging pipelines because of hydrate formation, wax/asphaltene precipitation, or scaling. , Hydrate flow assurance is a major technical concern by the flow assurance engineers in deep-water fields. Thermodynamic hydrate inhibitors (THIs) injecting or heating have been widely applied in flowlines to shift the operation condition outside of the hydrate formation boundary, making it thermodynamically unfavorable for hydrate formation. These methods are effective, but a large amount of additives is required to be injected and huge energy is needed for heating, which make them financially unattractive . Alternatively, a risk management method is presented to control hydrate blockage issues.…”
Section: Introductionmentioning
confidence: 99%
“…3−5 These methods are effective, but a large amount of additives is required to be injected and huge energy is needed for heating, which make them financially unattractive. 6 Alternatively, a risk management method is presented to control hydrate blockage issues. Low dosage hydrate inhibitors (LDHIs) including anti-agglomerants (AAs) and kinetic hydrate inhibitors (KHIs) are gaining more attention for advantages in low dosage and environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that the cost of injecting a thermodynamic inhibitor into the subsea flowlines can reach 50% of the total operating costs for offshore fields producing about 50 000 bbl/day water. 6 Several studies 5,7−9 have proposed a method called "underinhibition", in which the concentration of MEG in the water phase is reduced to a value lower than that required to fully avoid the hydrate formation. Creek et al 5 demonstrated that the hydrate inhibition performance of MEG in an under-inhibition system reduced the required MEG injection rate for the offshore gas field development.…”
Section: Introductionmentioning
confidence: 99%
“…However, handling a large amount of MEG or methanol in offshore and remote areas where the platforms are located would increase the operating cost significantly. It was estimated that the cost of injecting a thermodynamic inhibitor into the subsea flowlines can reach 50% of the total operating costs for offshore fields producing about 50 000 bbl/day water …”
Section: Introductionmentioning
confidence: 99%
“…A more practical and potentially cheaper solution for hydrate prevention or remediation is the injection of chemicals. This involves two major categories: thermodynamic hydrate inhibitors (THIs), such as methanol and glycol, and low dosage hydrate inhibitors (LDHIs) covering mainly kinetic hydrate inhibitors (KHIs) and antiagglomerates (AAs). THIs are still widely used in industry with the ability of directly lowering the hydrate–liquid–vapor equilibrium (HLVE) temperature or increasing the HLVE pressure.…”
Section: Introductionmentioning
confidence: 99%